2019
DOI: 10.1186/s13049-018-0583-1
|View full text |Cite
|
Sign up to set email alerts
|

Training and assessment of non-technical skills in Norwegian helicopter emergency services: a cross-sectional and longitudinal study

Abstract: BackgroundDeficient non-technical skills (NTS) among providers of critical care in helicopter emergency medical services (HEMS) is a threat to patient and operational safety. Skills can be improved through simulation-based training and assessment. A previous study indicated that physicians underwent less frequent training compared to pilots and HEMS crew members (HCM) and that all professional groups in Norwegian HEMS received limited training in how to cope with fatigue. Since then, training initiatives and a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
17
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(19 citation statements)
references
References 30 publications
(45 reference statements)
2
17
0
Order By: Relevance
“…There are a few simulation programs in HEMS that focus on issues like medical skills, NTS or CRM [4,6,7,9]. A study from the Norwegian HEMS showed that HEMS personnel lack simulation-based training and assessment of their NTS [12]. Various studies have demonstrated that HEMS personnel report a significant increase in self-assessed competency of NTS after simulation training [4,5,12].…”
Section: Existing Training Optionsmentioning
confidence: 99%
See 1 more Smart Citation
“…There are a few simulation programs in HEMS that focus on issues like medical skills, NTS or CRM [4,6,7,9]. A study from the Norwegian HEMS showed that HEMS personnel lack simulation-based training and assessment of their NTS [12]. Various studies have demonstrated that HEMS personnel report a significant increase in self-assessed competency of NTS after simulation training [4,5,12].…”
Section: Existing Training Optionsmentioning
confidence: 99%
“…A study from the Norwegian HEMS showed that HEMS personnel lack simulation-based training and assessment of their NTS [12]. Various studies have demonstrated that HEMS personnel report a significant increase in self-assessed competency of NTS after simulation training [4,5,12]. These NTS are essential to complement the technical skills needed in an intricate work setting such as mountain HEMS.…”
Section: Existing Training Optionsmentioning
confidence: 99%
“…It is a parameter of the scoring system called CURB-65, which is used especially in pneumonia patients [ 8 ]. It has been shown that its level is higher in pneumonia [ 9 ], chronic obstructive pulmonary disease [ 10 ], pancreatitis [ 11 ], acute myocardial infarction [ 12 ], heart failure [ 13 ], sepsis [ 14 ], and geriatric patients [ 15 ] with mortality. There have also been studies that showed a higher BUN level in COVID-19 patients with mortality [ 16 ].…”
Section: Introductionmentioning
confidence: 99%
“…Medical simulation is an integral part of medical education, post graduate training and continuous professional development [1]. Several studies have shown simulation-based training has a positive effect on patient outcomes [2,3].…”
Section: Introductionmentioning
confidence: 99%